HOW COMPETENCE USER IMPACT THE QUALITY MANAGEMENT INFORMATION SYSTEM - Christine Dwi Karya Susilawati (Prosiding International conference on Information Technology and Business (ICITB), 2016)
Management information system serves to present the necessary information management in decision making. MIS good quality should be supported by this MIS executor is personal that has a good competence. But in practice, users often overlooked competence to support the success of the system. This article examines how the competencies users literally have an impact on the quality of management information systems. Key Wordscompetence of users, the quality of management information systems